ANALISIS KETERKAITAN SEKTOR TANAMAN BAHAN MAKANAN DALAM PEREKONOMIAN WILAYAH KABUPATEN PEMALANG (DENGAN PENDEKATAN ANALISIS INPUT-OUTPUT) - Ropingi, Ropingi; Alusi, Alamah AI (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2006)
The aimed of this research was (a) to study the backward linkage and forward linkage of foodstuff plants towards another economic sector in Pemalang Regency, (b) to study how value of material requistion and service from output of another economic sector used up for production process of foodstuff plants sector in Pemalang Regency and (c) to study how value of the usage of goods and services from output of foodstuff plants used up for production process by another economic sector in Pemalang Regency. The research method used descriptive method, by using the data of I-O Table Pemalang Regency, The analysis used linkage analysis and descriptive analysis. The linkage analysis divided into the backward linkage and forward linkage. Descriptive analysis were Asses Input Ratio and Asses Request Ratio. The data employed are table data of input-output Central Java of year 2000, Domestic Product Regional Bruto of Pemalang Regency of year 2003, Pemalang in Number of year 2003. Result of the research was (a) indicates that food stuff plants have low backward linkage by looking at Spreading Index. Thus, It was low enough in using output of another economic sector in production process, (b) The output of foodstuff plants sector is highly needed by another economic sector in Pemalang Regency. It can be known by forward linkage value of foodstuff plant measuring with a high Index of Sensitivity Degree value, (c) According to descriptive analysis result, foodstuff plants sector have the lowest Asses Input Ratio. It means that foodstuff plants needs the lowest Asses input from output of production process.(d) Based on the analysis result of Asses Request Ratio, foodstuff plants sector have low Asses Request Ratio. Means that it has output used for input between another economic sectors was smaller than output used as the last consumption. Mostly, another economic sector used by foodstuff plants were industry sector and foodstuff plants sector. The other economic sector that uses foodstuff plants was industry sector and restaurant sector.